Direct-to-consumer fertility testing: utilization and perceived utility among fertility patients and reproductive endocrinologists. Issue 3 (March 2023) - Peipert, Benjamin J.; Harris, Benjamin S.; Selter, Jessica H.; Ramey-Collier, Khaila; Blenden, Randa; Unnithan, Shakthi; Erkanli, Alaattin; Price, Thomas M.
Abstract: Research Question: What is the utilization of direct-to-consumer fertility tests (DTCFT) among fertility patients? How does the perceived utility of DTCFT differ between patients and reproductive endocrinologists (REI)? Design: Infertility patients visiting the Duke Fertility Center between December 2020 and December 2021 were sent an electronic invitation to participate in a patient survey. Members of the Society of Reproductive Endocrinology and Infertility were also sent e-mail invitations to participate in the REI survey. DTCFT were defined as tests not ordered by a physician or performed at a physician's office, including calendar methods of ovulation prediction, urinary ovulation prediction kits, basal body temperature (BBT) monitoring, hormone analysis, ovarian reserve testing and semen analysis. Patients and REI were asked how likely they were to recommend a given DTCFT, on a 0–10 Likert scale. Results: In total, 425 patients (response rate 50.5%) and 178 REI (response rate 21.4%) completed the surveys. Patients reported the utilization of calendar methods of ovulation prediction (83.8%), urinary ovulation prediction (78.8%), BBT monitoring (30.8%), hormone analysis (15.3%), semen analysis (10.1%) and ovarian reserve testing (9.2%). REI rated the utility of all DTCFT significantly lower than patients did (average discordance –4.2, P < 0.001), except for urinary ovulation prediction, which REI gave a significantly higher score (discordance +1.0, P < 0.001). Prior pregnancy was significantly associated with home ovulation prediction utilization among patients (adjusted odds ratio 3.21, 95% confidence interval 1.2–9.83). Conclusions: Methods of ovulation prediction are commonly used by fertility patients. Significant discordance exists in the perceived utility of DTCFT between patients and REI. Patient education and guidelines are needed to better inform individuals considering DTCFT.